Polysteganus mascarenensis, a new sparid fish species from Mascarene Islands, Indian Ocean YUKIO IWATSUKI (Japan) & PHILLIP C. HEEMSTRA (South Africa) - Iwatsuki, Yukio; Heemstra, Phillip C. (Zootaxa, 2011)
A new sparid species, Polysteganus mascarenensis n. sp. (Perciformes; Sparidae) is described on the basis of three type specimens (578‒600 mm SL) from the Mascarene Islands, Indian Ocean. The species differs from the four known congeners of Polysteganus in having the following combination of characters: body moderately slender (depth 39% SL), scale rows between 10th dorsal-fin spine base and lateral line 6 ½, fewer lateral line scales 51‒54, snout broad, its length 2.2‒2.3 times orbit diameter in adults, inter-orbital area of adults with a bony bulge before and above eye (hyperostosis of frontal bones), forming a low median ridge; mouth large, jaws robust, especially upper jaw, caudal fin emarginate (nearly truncate if widely spread), head, body, and all fins generally reddish orange, no dark blotch or rows of small spots along scale rows on the body. The status and identification of congeneric nominal species are discussed, and a key to the species of Polysteganus is provided.